Near Term Suicide Risk Assessment: A Commentary on the Clinical Relevance of Protective Factors. (31st August 2020) - Berman, Alan L.; Silverman, Morton M.
Abstract : In this article we examine the clinical relevance of protective factors to the assessment and formulation of near-term risk of death by suicide. Contrary to current clinical belief and practice, we posit that there is no evidence base to support these factors as mitigating or buffering risk for suicide for the individual patient, especially in the near-term assessment of that suicide risk. We show that evidence-based protective factors derive from population-based studies and, applicably, have relevance to public health promotion/primary prevention and are significant in informing treatment/secondary prevention, but they lack evidence to support their often-proposed role in mitigating or buffering risk for suicide on an individual basis, especially when applied to the assessment of near-term risk of suicide. Accordingly, we argue for the need for empirical study of the role protective factors may or may not play in the formulation of a patient's risk for suicide and, in the interim, for clinical caution in assuming that protective factors have any significant buffering effect on a patient's level of near-term risk.